REVIEW AUDIT DENGAN PERSPEKTIF SYARIAH - Gardina Aulin Nuha (Universitas Muhammadiyah Jember, 2017)
Abstract: Shariah economic development gave rise to the existence of the new demands regarding the audit with the Shariah perspective. Moreover, the existence of some phenomena of lapses on Islamic entities lose trust over the Islamic entity. So the demand for Shariah-compliant audit became an important topic to be discussed. The purpose of this article is a review of the development related audit syariah. The first part of this article is about the introduction, the second section describes the history and development of the audit shariah. Next the third part describes the Accounting and Auditing Organization for Islamic Financial Institutions (AAOFI), fourth section regarding auditing and auditing of conventional Shariah and the last one was about the challenges faced by the audit syariah, and the fifth part is conclusion.Keywords: Audit Review, Audit Shariah, Islamic Entities, Shariah Economic